A Study Of Attitude And Graduation In English And Vietnamese Economic Newspaper Articles: An Appraisal Approach - Th.S Võ Nguyễn Thùy Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The thesis aims at investigating and analyzing the use of evaluative language 3 Attitude and Graduation in English and Vietnamese economic opinion articles (EEOAs and VEOAs) in the light of Appraisal theory by Martin and White (2005). To conduct the study, from the discourse semantics approach, the descriptive research was adopted, seeking the qualitative and quantitative information to the three research questions on examining semantic features and lexicogrammatical realizations of Attitude and Graduation in EEOAs and VEOAs as well as comparing the similarities and differences in writers9 stances in terms of semantic features and lexicogrammatical realizations of Attitude and Graduation between EEOAs and VEOAs. The data collection included 50 EEOAs and 50 VEOAs. Semantically, the findings revealed that all subtypes of Attitude including Appreciation, Judgement and Affect were realized in EEOAs and VEOAs, with the frequency of 2517 and 1592 respectively. Despite the difference in the frequency of Attitude, bo